A proposal on a catalyst for the reaction methane + water => methanol + hydrogen - Ragnar Larsson (Open Journal of Chemistry - Peertechz Publications, 2021)
Based on the concepts and vocabulary of the SET model of catalysis a discussion is performed on what properties should characterize a catalyst promoting a reaction such as the one in the title, i.e., the production of methanol from methane in a non-oxidative environment. It is found that the n1 vibration of water (3652 cm-1 ) and the ny4 vibration of methane (1306 cm-1) interact in resonance.  This means that 1306/3652 = 0.3576 whereas 5:14 = 0.3571. The difference between these two ratios is thus 0.0005. One notes that both frequency-values contain a factor of 1306/5 = 261 cm-1. The conclusion is that also the catalyst must take part in and promote that resonance, containing the same factor, 261 cm-1.